Mutu Sekolah Berdasarkan Kreativitas dan Budaya Kerja Guru - S, Sriyanto (Universitas Muhammadiyah Purwokerto, 2015)
Abstract. This study was aimed to analyze the relationship between the quality of schools based on creativity and the work culture of teachers at the primary school level. At the primary school level the phenomenon of teachers as educators and administrative personnel as well, and must master the entire field of science provide workload is quite high. While it demands professionalism of teachers today has become imperative, where teachers must have four competence as a prerequisite for becoming an educator who has been mandated by law. This research was conducted in Banjar District by taking a sample of teachers in 16 elementary schools, with a sample of 124 peoples. The data were collected using a questionnaire, which is then processed using SPSS. The result showed that the hypothesis statement there is a significant relationship between the creativity of teachers to school quality is accepted. Statements contained hypothesis cultural relations work on the quality of school teachers accepted. While the statement of the hypothesis that together the relationship between creativity and the work culture of teachers to school quality is acceptable. This study analyzed the relationship is generally variable, while the follow-up to improve the quality of schools required further research.Keywords: quality of school, teacher creativity, work cultureAbstrak. Penelitian ini bertujuan untuk menganalisis hubungan mutu sekolah berdasarkan kreativitas dan budaya kerja guru di tingkat sekolah dasar. Di level sekolah dasar fenomena tentang guru sebagai pendidik dan tenaga administratif sekaligus, dan harus menguasai seluruh bidang ilmu memberikan beban kerja yang cukup tinggi. Sementara itu tuntutan profesionalisme guru saat ini sudah menjadi keharusan, dimana guru harus memiliki empat kompetensi sebagai satu syarat untuk menjadi pendidik yang sudah diamanatkan dalam undang-undang. Penelitian ini dilakukan di Kota Banjar dengan mengambil sampel guru di 16 sekolah dasar, dengan jumlah sampel 124 orang. Data dikumpulkan dengan menggunakan angket, yang kemudian diolah menggunakan program SPSS. Hasil analisis data menunjukkan bahwa pernyataan hipotesis terdapat hubungan signifikan antara kreativitas guru terhadap mutu sekolah dapat diterima. Pernyataan hipotesis terdapat hubungan budaya kerja guru terhadap mutu sekolah diterima. Sedangkan pernyataan hipotesis bahwa secara bersama-sama terhadapat hubungan antara kreativitas dan budaya kerja guru terhadap mutu sekolah dapat diterima. Penelitian ini secara umum menganalisis hubungan variable, sedangkan untuk tindak lanjut peningkatan mutu sekolah diperlukan penelitian lanjutan.Keywords: mutu sekolah, kreativitas guru, budaya kerja